A volatile organic compound free unibody triboelectric nanogenerator and its application as a smart green track. (January 2023) - Wu, Wenjie; Wen, Shipeng; Wei, Yi; Ruan, Lu; Li, Fanzhu; Cao, Xia; Wang, Zhong Lin; Zhang, Liqun
Abstract: Exercise not only builds up one's health but also reduces the risk of developing diseases including type 2 diabetes, cancer, and cardiovascular diseases. Being one of the most classic and popular sports, track and field will does harm to one's knees if not enough buffering is provided by the track. In a world that is urgently calling for environmental protection while steadily embracing the internet of things, environment-friendliness and smartness should also be taken into consideration when designing an optimized track. Hitherto most of the tracks are made of in-situ casted polyurethane (PU) and prefabricated ethylene propylene diene monomer (EPDM), which leads to emission of volatile organic compounds (VOCs) including polycyclic aromatic, hydrocarbons (PAHs), phthalates etc. In the meantime, intelligentization is seldom taken in consideration when designing and fabricating a track. Herein, we introduce an unibody silicone rubber-based track featured by adequate buffering providing, environment-friendliness, energy harvesting and sensing with an expected service life of about several decades. We also established a finite element model of the track to assess its deformation and energy dissipation capabilities. This track can work as a triboelectric nanogenerator (TENG) whose current density is 703  n A / cm 2, serving as both an electric generator and a gait sensor. It will give guidance to the development of unibody TENG and open a new avenue for the next generation of self-powered smart track. Graphical Abstract: In a world that is urgently calling for environmental protection while steadily embracing the internet of things, environment-friendliness and smartness should also be taken into consideration when designing the next-generation of track. A silicone rubber-based TENG-based smart track featured by adequate buffering providing, environment-friendliness, energy harvesting and sensing with an expected service life of about several decades is designed and manufactured in this work. We also established a finite element model of the track to assess its deformation and energy dissipation capabilities. This track can work as a triboelectric nanogenerator (TENG), whose current density is 703  n A / cm 2, serving as both an electric generator and a gait sensor. It will give guidance to development of unibody TENG and open a new avenue for the next generation of self-powered smart track. ga1 Highlights: A VOC-free unibody elastomer-based triboelectric nanogenerator which is tough enough for an outdoor track. Establishment of a finite element model of the track to assess its deformation and energy dissipation capabilities. A smart track system which can sever a gait sensor and training monitor is designed and fabricated.